Review of taxonomic challenges in cryptic species identification (Zoological Records and Reviews, 2022)
Cryptic species -- morphologically similar but genetically and reproductively distinct lineages -- represent one of the mostsignificant and persistent challenges in modern taxonomy and biodiversity science. As molecular tools have becomeroutine in systematic biology, the pace of cryptic species discovery has accelerated dramatically, with estimatessuggesting that cryptic diversity may constitute 20-40% of all animal species in morphologically conservative lineages.This review synthesises current knowledge of cryptic species prevalence, identification methods, and taxonomicconsequences across five major animal groups -- freshwater fishes, amphibians, insects, marine invertebrates, andparasitic helminths -- drawing on a meta-analysis of 284 case studies published between 2000 and 2021. Mean crypticspecies prevalence across groups is 28.4% of morphologically circumscribed species, with parasitic helminths showingthe highest prevalence (42.8%) and marine fishes the lowest (18.4%). Integrative taxonomic approaches combiningmolecular, morphometric, acoustic, and ecological data demonstrate the highest accuracy for cryptic species delimitation,outperforming single-character methods by 34.8 percentage points. Molecular barcoding (COI) correctly identifies crypticspecies in 84.2% of cases when calibrated reference libraries are available. The conservation implications of crypticdiversity are profound: 48.4% of cryptic species identified from nominal widespread taxa qualify as Threatened underIUCN criteria when assessed on their true restricted ranges. We provide a decision framework for practitioners navigatingcryptic species identification and recommend minimum standards for evidence required before formal speciesdescription.
Keywords: cryptic species; integrative taxonomy; DNA barcoding; species delimitation; morphological conservatism; biodiversity underestimate; COI; conservation; molecular systematics; species concepts